Invitation strategy of vaginal HPV self-sampling to improve participation in cervical cancer screening: a systematic review and meta-analysis of randomized trials - Ho Yan Wong; Eliza Lai-yi Wong (BMC, 2024)
Abstract Background Human papillomavirus (HPV) self-sampling is recognized as a feasible option for enhancing screening for cervical cancer, particularly among hard-to-reach women. The magnitude of the effectiveness of screening participation under different invitation strategies was reported. This review seeks to compare the effectiveness of invitation strategies in increasing screening participation of HPV self-sampling across diverse study settings. Methods A systematic literature search was conducted in Embase, MEDLINE, and PubMed in April 2023. Articles were included if (1) their target participants were aged between 25 and 70 years; (2) participants in the intervention arm were randomized to receive HPV self-sampling devices through various invitation strategies; (3) participants in the control arm who either received invitations for cervical cancer screening other than HPV self-sampling or opportunistic screening as usual care; (4) studies that provided sufficient data on screening participation in HPV self-sampling as outcome measured. The study design of the included articles was limited to randomized controlled trials. Results A total of 15 articles were included in this review. Invitation strategies of disseminating HPV self-sampling devices included opt-out and opt-in. Meta-analysis revealed screening participation in the self-sampling group was significantly greater than control arm (OR 3.43, 95% CI 1.59-7.38), irrespective of the invitation strategy employed. Among invitation strategies, opt-out appeared to be more effective on increasing screening participation, compared to control and opt-in strategy (opt-out vs. control OR 3.91, 95% CI 1.82-8.42; opt-in vs. control OR 1.34, 95% CI 0.28-6.39). Conclusions Opt-out strategy is more successful at improving screening participation compared to opt-in and routine invitation to cervical screening. It is therefore a promising way to improve participation in cervical cancer screening. The findings of this review provide important inputs to optimize strategies for inviting women to participate in vaginal HPV self-sampling across the study setting, thus improving participation in cervical cancer screening.